Method for reducing consumption rate of active metal in anode protection method
By pretreating the reactive metal and coating it with conductive binder and photocatalytic material to carry out photocatalytic reaction, the problem of rapid consumption of reactive metals in the anodic protection method is solved, thereby extending the service life of the reactive metals and reducing the replacement frequency.
Patent Information
- Application Number
- CN202511091841.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-11-21
AI Technical Summary
In existing technologies, reactive metals are consumed rapidly in anodic protection methods, leading to frequent replacements and affecting equipment structural safety and operational efficiency.
The active metal is pretreated to form a galvanic cell reaction, and then coated with a conductive binder and a photocatalytic material to reduce the consumption rate of the active metal through a photocatalytic reaction.
It effectively extends the service life of reactive metals, reduces the frequency of replacement and maintenance costs, and seamlessly integrates with existing anti-corrosion systems, reducing the difficulty and cost of technical application.
Smart Images

Figure CN120989625A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal corrosion protection and relates to a method for reducing the consumption rate of active metals in anodic protection. Background Technology
[0002] In humid environments, especially marine environments, electrochemical corrosion of metallic materials is highly likely to occur and is often very severe. During electrochemical corrosion, countless tiny galvanic cells form on the metal surface. In the anodic region, the metal loses electrons and undergoes an oxidation reaction, resulting in corrosion and dissolution; in the cathodic region, a reduction reaction occurs, typically where oxygen gains electrons to generate hydroxide ions (OH-). - This microscopic galvanic cell reaction continues, which macroscopically manifests as the gradual damage to metal materials, such as corrosion and perforation, seriously affecting the service life and safety of metal structures.
[0003] Sacrificial anode protection is a technique that prevents corrosion of metal structures through electrochemical principles, and it is widely used in corrosion protection engineering for facilities such as ships, pipelines, and storage tanks. Its principle is based on the galvanic cell principle in electrochemistry, where a more reactive metal (anode) actively "sacrifices" itself to protect the metal being protected (cathode) from corrosion. Among the many metallic materials that can be used for sacrificial anode protection, zinc (Zn) is often used for corrosion protection in seawater environments (such as ship hulls and docks) due to its suitable driving voltage (-0.76 V). A suitable driving voltage means that when zinc forms a galvanic cell with the protected metal, it can provide a stable and appropriate current, ensuring effective corrosion protection without affecting the normal operation of the entire system due to excessively large or small currents. It is the most widely used and consumed reactive metal among all reactive metals.
[0004] When the reactive metal zinc (Zn) is used as an anode in a corrosion protection system, it corrodes preferentially, releasing electrons that are consumed. The protected metal, acting as the cathode, accepts these electrons, inhibiting its own corrosion reaction. This leads to the gradual consumption of the anode material, requiring periodic replacement when 20%–30% remains. In practical applications, zinc anodes are typically welded or bolted directly to the protected structural components (such as ship keels or critical parts of offshore platforms) for easy replacement when needed. However, higher replacement frequency inevitably impacts the structural safety and operational efficiency of the protected equipment. Therefore, reducing the consumption rate of reactive metals and decreasing their replacement frequency are crucial measures to improve the operational efficiency of offshore platforms or equipment and reduce safety hazards. Summary of the Invention
[0005] The purpose of this invention is to provide a method for reducing the consumption rate of active metals in anodic protection, thereby solving the problems of rapid consumption and high replacement frequency of anode materials in the prior art.
[0006] To achieve the above objectives, the present invention employs the following technical solution: A method for reducing the consumption rate of active metals in anodic protection includes: Pretreatment of reactive metals; The pretreated active metal is used as the anode and connected to the steel cathode to form a circuit, thus constructing a galvanic cell reaction. A conductive binder is coated onto the surface of an active metal to form a conductive adhesive layer. A photocatalytic material is then uniformly coated onto the surface of the conductive adhesive layer to obtain a photocatalytic coating. By placing the photocatalytic coating under light to carry out a photocatalytic reaction, the consumption rate of active metals can be reduced.
[0007] Furthermore, the pretreatment method for reactive metals is as follows: The surface of the reactive metal is polished clean, and then subjected to alkali washing, alcohol washing and water washing in sequence to remove impurities from the surface of the reactive metal. Impurities include oxide layers, dust, and oil.
[0008] Furthermore, the conductive adhesive is a carbon-based conductive adhesive, a silver-based conductive adhesive, or an epoxy conductive adhesive.
[0009] Furthermore, the thickness of the conductive adhesive layer is 0.1~1500 μm.
[0010] Furthermore, the average impedance of the conductive adhesive layer is less than 100 Ω·cm.
[0011] Furthermore, the photocatalytic material is g-C3N4, TiO2, SrTiO3, or a TiO2 / g-C3N4 heterojunction.
[0012] Furthermore, the photocatalytic material has a reduction potential greater than -0.76 V and an average particle size of less than 1000 μm.
[0013] Furthermore, the thickness of the photocatalytic coating is 1 to 3 times the particle size of the photocatalytic material.
[0014] Furthermore, the number of coating layers for the photocatalytic coating is 1 to 3.
[0015] Furthermore, the illumination is sunlight, incandescent lamps, or fluorescent lamps with wavelengths between 200 and 800 nm.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for reducing the consumption rate of active metals in sacrificial anode protection. By using a pretreated active metal as the anode and connecting it to the steel cathode to form a galvanic cell reaction, a conductive binder is coated onto the surface of the active metal, followed by a uniform coating of a photocatalytic material to obtain a photocatalytic coating. The photocatalytic coating is then placed under light to undergo a photocatalytic reaction, effectively reducing the corrosion and dissolution of the active metal in the galvanic cell reaction, thus lowering the consumption rate. This invention builds upon existing sacrificial anode protection methods. Without altering the connection method between the substrate and the active metal in existing sacrificial anode protection methods, it uniformly coats the active metal surface with a photocatalytic material, reducing the consumption rate and extending the service life of the active metal in sacrificial anode protection. This is particularly beneficial for extending the service life of zinc blocks in the marine industry, reducing the frequency of replacement and maintenance costs. Furthermore, in practical applications, no large-scale modification or adjustment of existing equipment and processes is required, allowing seamless integration with existing corrosion protection systems, significantly reducing the difficulty and cost of technology application. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a physical image of the Zn plate of the present invention.
[0019] Figure 2 This is a physical image of the steel sheet of the present invention.
[0020] Figure 3 This is a physical diagram of the connection between the steel sheet and the zinc plate of the present invention. Figure 4 This is a diagram illustrating the experimental process of Embodiment 1 of the present invention.
[0021] Figure 5 This is a diagram illustrating the experimental process of Embodiment 2 of the present invention.
[0022] Figure 6 This is a diagram illustrating the experimental process of Embodiment 3 of the present invention.
[0023] Figure 7 This is a diagram illustrating the experimental process of Embodiment 4 of the present invention.
[0024] Figure 8 This is a diagram illustrating the experimental process of Embodiment 5 of the present invention.
[0025] Figure 9 This is a diagram illustrating the experimental process of Embodiment 6 of the present invention.
[0026] Figure 10 This is a diagram illustrating the experimental process of Embodiment 7 of the present invention.
[0027] Figure 11 This is a diagram illustrating the experimental process of Embodiment 8 of the present invention.
[0028] Figure 12 This is a diagram illustrating the experimental process of Embodiment 9 of the present invention.
[0029] Figure 13 This is a diagram illustrating the experimental process of Embodiment 10 of the present invention.
[0030] Figure 14 The photocurrent spectra of the g-C3N4, TiO2, SrTiO3 and TiO2 / g-C3N4 heterojunctions of the present invention are shown.
[0031] Figure 15 Impedance spectra of g-C3N4, TiO2, SrTiO3, and TiO2 / g-C3N4 heterojunctions of the present invention.
[0032] Figure 16 The graph shows the weight reduction rate of the zinc plate and steel sheet connection of the present invention under natural conditions (number 1) and the weight reduction rate of Examples 1 to 10 (numbers 2 to 11). Detailed Implementation
[0033] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0035] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0036] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0037] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0038] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0039] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0040] The invention will now be described in further detail with reference to the accompanying drawings: This invention provides a method for reducing the consumption rate of active metals in anodic protection, specifically including the following steps: Step 1: Pretreatment of reactive metals.
[0041] Polish the surface of the reactive metal clean, and then wash it several times with alkali, alcohol and water to remove the oxide layer, dust and oil and other impurities from the surface of the reactive metal.
[0042] Step 2: Use the pretreated reactive metal Zn plate as the anode, such as... Figure 1 As shown, steel used as a cathode in ships, surface work platforms, or easily corroded areas, such as... Figure 2 As shown, the pretreated active metal is connected to the steel to form a pathway, constructing a galvanic cell reaction. The active metal acts as the anode and is continuously consumed by oxidation, while the protected steel is not corroded. The active metal can be placed together with the protected steel and fixed with bolts, or they can be placed in different locations, but it is essential to ensure that the active metal and the protected steel form a pathway.
[0043] Step 3: Apply a layer of conductive adhesive to the connected reactive metal surfaces from Step 2 to form a conductive adhesive layer. The conductive adhesive can be carbon-based conductive adhesive, silver-based conductive adhesive, or epoxy conductive adhesive. The thickness of the conductive adhesive layer is 0.1~1500μm, and the average impedance is less than 100 Ω·cm. Higher impedance results in less effective protection for the reactive metal.
[0044] Step 4: Grind and sieve the photocatalytic material with a reduction potential greater than -0.76 V to obtain a photocatalytic material with a uniform particle size and an average particle size of less than 1000 μm. Excessively large particle size will reduce the migration efficiency of excited electrons to the active metal surface, thus decreasing the protective performance. Uniformly coat the photocatalytic material onto the surface of the conductive adhesive layer from Step 3 to obtain a photocatalytic coating. Spraying is generally used as the coating method, as it yields good results, but is not limited to spraying. The thickness of the photocatalytic coating should be 1 to 3 times the particle size of the photocatalytic material, and the number of coating layers should be 1 to 3. The thicker the photocatalytic coating, the greater the resistance to the migration of excited electrons to the active metal surface, and the worse the protective performance.
[0045] Among them, the photocatalyst materials are g-C3N4, TiO2, SrTiO3, or TiO2 / g-C3N4 heterojunctions, which are simple to prepare, low in cost, stable in photothermal properties, and environmentally friendly. The photocurrent spectra of g-C3N4, TiO2, SrTiO3, or TiO2 / g-C3N4 heterojunctions are shown below. Figure 14 As shown in the figure, TiO2 produces the smallest photocurrent, while TiO2 / g-C3N4 produces the largest. This indicates that the construction of the heterojunction facilitates the separation of photogenerated carriers, allowing more excited electrons to be transported to the Zn plate surface. This suppresses the consumption of free electrons on the Zn plate, thereby reducing the consumption rate of the active metal. The impedance spectra of g-C3N4, TiO2, SrTiO3, and TiO2 / g-C3N4 heterojunctions are shown in the figure. Figure 15 As shown in the figure, g-C3N4 has the largest impedance, indicating that the migration resistance of excited electrons generated by g-C3N4 is the greatest. The construction of TiO2 / g-C3N4 heterojunction can also effectively reduce the migration resistance of electrons, improve electron mobility, and reduce the consumption rate of active metals.
[0046] Step 5: Place the photocatalytic coating prepared in Step 4 under light to carry out the photocatalytic reaction. The light source can be sunlight, incandescent lamp or fluorescent lamp, etc., with a wavelength range of 200~800 nm. The reduction potential of the excited electrons generated by the photocatalytic coating is within a certain range. The current intensity can be adjusted according to the usage conditions. The photocurrent can supplement the current of the active metal, thereby reducing the consumption rate of the active metal.
[0047] This invention is based on the fact that the reduction potential of the active metal Zn is -0.76 V, which is higher than that of Fe (-0.46 V). Zn protects Fe from corrosion by consuming its own electrons through oxidation. This invention utilizes excited electrons (reduction potential higher than -1.01 V) generated by photocatalytic materials, which have a stronger reducing ability, as a supplementary current to reduce the consumption rate of Zn, extend its lifespan, and lower the cost of metal protection.
[0048] The present invention will be further described in detail below through specific embodiments: Example 1: like Figure 4 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of graphite conductive adhesive with a thickness of 1500 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, a layer of g-C3N4 particles with an average particle size of 1000 μm was sprayed on the graphite conductive adhesive. Finally, the Zn plate with g-C3N4 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0049] Example 2: like Figure 5 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of graphite conductive adhesive with a thickness of 1500 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, two layers of g-C3N4 particles with an average particle size of 1000 μm were sprayed on the surface of the graphite conductive adhesive. Finally, the Zn plate with g-C3N4 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0050] Example 3: like Figure 6 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of graphite conductive adhesive with a thickness of 1500 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, three layers of g-C3N4 particles with an average particle size of 1000 μm were sprayed on the surface of the graphite conductive adhesive. Finally, the Zn plate with g-C3N4 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0051] Example 4: like Figure 7As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of graphite conductive adhesive with a thickness of 0.1 μm and an impedance of 100 Ω·cm was sprayed onto the surface of the Zn sheet. Then, a layer of g-C3N4 particles with an average particle size of 0.1 μm was sprayed onto the graphite conductive adhesive. Finally, the Zn plate with g-C3N4 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0052] Example 5: like Figure 8 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of graphite conductive adhesive with a thickness of 1000 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, a layer of g-C3N4 particles with an average particle size of 1000 μm was sprayed on the graphite conductive adhesive. Finally, the Zn plate with g-C3N4 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0053] Example 6: like Figure 9 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of silver conductive adhesive with a thickness of 1000 μm and an impedance of 100 Ω·cm was sprayed onto the surface of the Zn sheet. Then, a layer of g-C3N4 particles with an average particle size of 0.1 μm was sprayed onto the silver conductive adhesive. Finally, the Zn plate with g-C3N4 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0054] Example 7: like Figure 10 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of epoxy conductive adhesive with a thickness of 1000 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, a layer of g-C3N4 particles with an average particle size of 0.1 μm was sprayed on the epoxy conductive adhesive. Finally, the Zn plate with g-C3N4 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0055] Example 8: like Figure 11As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of epoxy conductive adhesive with a thickness of 1000 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, three layers of TiO2 particles with an average particle size of 0.1 μm were sprayed on the epoxy conductive adhesive. Finally, the Zn plate with TiO2 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0056] Example 9: like Figure 12 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of epoxy conductive adhesive with a thickness of 1000 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, three layers of SrTiO3 particles with an average particle size of 0.1 μm were sprayed on the epoxy conductive adhesive. Finally, the Zn plate with SrTiO3 particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0057] Example 10: like Figure 13 As shown, the surface of the Zn sheet was polished clean and then washed three times with alkali, alcohol, and water. The Zn sheet was connected to the steel sheet with a wire to form a conductive path. First, a layer of epoxy conductive adhesive with a thickness of 1000 μm and an impedance of 100 Ω·cm was sprayed on the surface of the Zn sheet. Then, three layers of TiO2 / g-C3N4 heterojunction particles with an average particle size of 0.1 μm were sprayed on the epoxy conductive adhesive surface. Finally, the Zn plate coated with TiO2 / g-C3N4 heterojunction particles was placed under an incandescent lamp to carry out a photocatalytic reaction to reduce the consumption rate of the Zn plate.
[0058] The weight loss rate of zinc plates under natural conditions and the weight loss rate under the conditions of Examples 1-10 of the present invention are compared as follows: Figure 16 As shown, Figure 16 Comparing the weight loss rate of No. 1 under natural conditions with the weight loss rates of No. 2 to 11 under the conditions of Examples 1 to 10, it can be seen that the weight loss rate of the zinc plate coated with the photocatalytic coating is significantly lower than that of the zinc plate without the photocatalytic coating. This is because the excited electrons generated by the photocatalytic coating migrate to the zinc plate through the conductive adhesive, inhibiting the consumption of the zinc plate and thus significantly reducing the weight loss rate of the zinc plate. This shows that the present invention can effectively reduce the consumption rate of active metals.
[0059] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for reducing the consumption rate of active metals in anodic protection, characterized in that, include: Pretreatment of reactive metals; The pretreated active metal is used as the anode and connected to the steel cathode to form a circuit, thus constructing a galvanic cell reaction. A conductive binder is coated onto the surface of an active metal to form a conductive adhesive layer. A photocatalytic material is then uniformly coated onto the surface of the conductive adhesive layer to obtain a photocatalytic coating. By placing the photocatalytic coating under light to carry out a photocatalytic reaction, the consumption rate of active metals can be reduced.
2. The method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The pretreatment method for reactive metals is as follows: The surface of the reactive metal is polished clean, and then subjected to alkali washing, alcohol washing and water washing in sequence to remove impurities from the surface of the reactive metal. Impurities include oxide layers, dust, and oil.
3. The method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The conductive adhesive is a carbon-based conductive adhesive, a silver-based conductive adhesive, or an epoxy conductive adhesive.
4. The method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The thickness of the conductive adhesive layer is 0.1~1500 μm.
5. The method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The average impedance of the conductive adhesive layer is less than 100 Ω·cm.
6. The method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The photocatalytic material is g-C3N4, TiO2, SrTiO3, or a TiO2 / g-C3N4 heterojunction.
7. The method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The photocatalytic material has a reduction potential greater than -0.76 V and an average particle size of less than 1000 μm.
8. The method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The thickness of the photocatalytic coating is 1 to 3 times the particle size of the photocatalytic material.
9. A method for reducing the consumption rate of active metals in anodic protection according to claim 1, characterized in that, The number of coating layers for photocatalytic coating is 1 to 3.
10. A method for reducing the consumption rate of active metals in anodizing protection according to claim 1, characterized in that, The illumination is sunlight, incandescent lamps, or fluorescent lamps with wavelengths between 200 and 800 nm.